2020
DOI: 10.1590/1981-5271v44.1-20190069
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas de Depressão, Ansiedade e Estresse em Estudantes de Medicina e Estratégias Institucionais de Enfrentamento

Abstract: Resumo: Introdução: Este estudo teve como propósito estimar a prevalência de sintomas de estresse, depressão e ansiedade dos estudantes de Medicina da Universidade Federal do Rio Grande do Norte (UFRN), associando-os com outros fatores. Métodos: Trata-se de um estudo quantitativo epidemiológico, do tipo transversal. Participaram desta pesquisa estudantes de Medicina da UFRN, distribuídos equitativamente entre os diferentes períodos do curso. Entregaram-se 288 questionários, no entanto validaram-se 279, os de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
58

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 23 publications
3
20
0
58
Order By: Relevance
“…Consistent with the literature, anxiety and depression symptoms were more frequent among students in the 3 rd , 5 th and 9 th semesters of medical school. Considering the course cycles, the basic one showed a higher prevalence than the other cycles, similar to that found by Costa et al (2020) 23 . Upon entering the university, students are faced with an environment that is completely different from what they had been experiencing in the previous years of study 45,46 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with the literature, anxiety and depression symptoms were more frequent among students in the 3 rd , 5 th and 9 th semesters of medical school. Considering the course cycles, the basic one showed a higher prevalence than the other cycles, similar to that found by Costa et al (2020) 23 . Upon entering the university, students are faced with an environment that is completely different from what they had been experiencing in the previous years of study 45,46 .…”
Section: Resultssupporting
confidence: 88%
“…Symptoms were minimal in 259 (56.6%) and absent in 34 (7.4%) students (Chart 1). 23 . However, these same authors indicated a prevalence of symptoms of depression between 8.2% and 34.6%, therefore, lower than that of the present investigation (36.0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high number of hours, excess of bad nights, and the construction of a career that does not admit mistakes are points that have a great potential impact on the quality of life of medical students, being, therefore, quality of life defined as "the perception of individual of his insertion in life, in the context of the culture and value systems in which he lives and in relation to his goals, expectations, standards, and concerns " [3]. This concept involves the entire context in which the individual is inserted based on social determinants and, analyzing the conjuncture of a student in the medical field, a complex process is perceived, in which responsibilities carry daily anxieties and anxieties, which directly imply their physical and mental health, significantly increasing the chance of developing important psychological disorders due to stress, including low self-esteem and body dissatisfaction, which are triggers for the development of eating disorders [10][11][12][13][14].…”
Section: Research Articlementioning
confidence: 99%
“…Além disso, grande parte dos universitários se encontram na faixa etária de 15 a 29 anos, período em que o suicídio se destaca como segunda maior causa de mortalidade (GARLOW et al, 2008;WHO, 2014). A literatura aponta que sentimentos e comportamentos suicidas são relativamente comuns nesse grupo (GARLOW et al, 2008;RAMÔA et al, 2017;HIDALGO-RASMUSSEN et al, 2019;COSTA et al, 2020;CHANG et al, 2017;CHANG et al, 2019;FLESCH et al, 2020). Também é preocupante o fato de que os universitários com histórico comportamento suicida ou autolesivo podem permanecer sintomáticos e apresentando risco elevado para novas tentativas de suicídio (ALBUQUERQUE; BORGES; MONTEIRO, 2019).…”
Section: Lista De Abreviaturasunclassified